THE EFFECT OF PRODUCTION COST TO NET PROFIT; A CASE STUDY OF PT. INDORAMA SYNTHETICS TBK - Wulandari, Mutia; Abror, Ahmad; Inggita, Manohara (Emerging Markets : Business and Management Studies Journal, 2016)
Production is the largest cost part of the company. A production process at each company would require a considerable cost. ?Production costs are costs incurred in order to process raw materials into products and goods are ready for sale. This study aims to determine how much influence the cost of production to net income. Abstract This study used descriptive method with quantitative approach. The population used in this study was the financial statements; costs production statement, Profit and loss statement from the year 2010-2014 of PT. Indorama Synthetics Tbk. Sample selection has done by using purposive sampling method with amount of data processed 6 years. The data used are primary data. Data were tested using SPSS 21.0, the data analysis used was simple regression analysis, correlation analysis, determination coefficient analysis and hypothesis test using parameter significance test (t test). The result of this research show that partially production cost have a significant effect to net profit. Based on t-test known that the hypothesis was accepted since the t count was higher than t-table value. The t-count was equal to 3,095, while the t-table was 2,776, with a significant value of 0.036 smaller than 0.05, which means that production costs significantly affect net income at PT Indorama Synthetics Tbk.